PARTISIPASI DAN PERSEPSI MASYARAKAT DALAM UPAYA MENJAGA MENGELOLA LINGKUNGAN HIDUP DAN MEMPERTAHANKAN PREDIKAT KOTA BERSIH - Ricky Arief Budiman; Zulfan Saam; Thamrin Thamrin (Jurnal Ilmu Lingkungan, 2013)
Issues of garbage are a big problem in nearly all past of world, including in Indonesia.Tanjungpinang as a capital of Kepulauan Riau Province is also facing a big problem aboutgarbage, such as less adequuate of landfield, less hygiene of infrastructure and soon.Tanjungpinang has several times received a clean city award which was granted by centralgovernment through the ministry of environment in order to make urban environment clean,beautiful, and immaculate. However Adipura Award had received by tanjungpinang 10 timesfrom 1991 until 2012 ,the aimsof this study to identify and analyze the characteristics, andthe perceived level of public participation Tanjungpinang in maintaining, managing andmaintaining the environment around Adipura Award. The study was conducted over 2(two)months from September to October 2012 through the deployment quesinoner to people wholive or work in the points Adipura Tanjungpinang set by the Ministry of Environment Todetermine the relationship between variables perception dan participation is used Spearmancorrelation coefficient calculation Range analysis. The results showed that thecharacteristics (age, education, income, occupation) are in both categories, as well as a highlevel of public perception, but for the level of participation is low. This result maybe cause bythe lack of involvement of the community in hygiene programs implemented by thegovernment, at least the number of points monitored Adipura assessment so as notrepresentative and characteristic of urban society tends individualistic.